THE TRADITION OF YASINAN IN INDONESIA - Akhmad Sagir; Muhammad Hasan (Khazanah: Jurnal Studi Islam dan Humaniora, 2021)
Surah Yasin is a surah often recited in various religious activities in Indonesian society. Yasin a considered a surah that has many benefits. The tradition of reciting Yasin is a routine practice done by Muslims, especially in Indonesia. However, the recitation of Yasin in Indonesia is encountered in various forms in religious rituals. Therefore, the writing was based on people gathering to recite Yasin. It can be seen that the reciting Yasin is not only in the culture but the Islamic values that are instilled. This study aims to conduct a literature review study on the living Qur’an use of Yasin in Indonesia. The ATLAS.ti application version 9.0.20.0 was used to assist in analysing existing data. This research method used was reviewing the living Qur’an literature, including 1) the first stage: planning review, 2) the second stage: the implementation of the review, and 3) the last stage: presentation of results. The researcher found 78 articles from the google scholar index source, and 28 papers were read and analysed in this study. The findings showed Yasin’s function for public belief and forms of traditions cultivated in Indonesia’s living Qur’an. These findings resulted in the reciting of Yasin as a practice cultured by the community. Also, the culture of reciting Yasin becomes a sacred ritual and full of meaning in every activity. It is suggested that future research provides a specific knowledge contribution to reciting Yasin in Indonesia.